Peranan Pelanggan Dalam Produksi Industri Kerajinan Perak Di Kota Denpasar - I Gusti Ayu Athina Wulandari; A.A. Gede Agung Parameswara (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2020)
The aim of this study is to analyze the role of regular customers owned by each unit of the silver handicraft business. Furthermore, this study also looks at how the influence of the use of production factors such as raw materials, capital and labor in the silver handicraft business on the number of permanent customers owned and on the production of silver handicrafts. This study uses primary data collected through questionnaires and analyzed using path analysis. In-depth interviews were conducted to justify the results of the analysis. Based on the results of the analysis, raw materials have a positive and significant effect while capital and labor do not have a significant effect on customers. Raw materials and labor have positive and significant effects while customers and capital have negative and significant effects on production.